Myth, history, and the origins of al-Andalus: a historiographical essay. Issue 3 (2nd September 2019) - Wolf, Kenneth Baxter
ABSTRACT: This essay juxtaposes two recent efforts to demythologize the history of the origins of al-Andalus. Alejandro García Sanjuán has called into question the continued usefulness of reconquista as a historical model, while Emilio González Ferrín has gone further, challenging the very notion of an "Islamic conquest, " which he regards as another misleading holdover from the past. Considering these two approaches side by side allows for a deeper appreciation of the challenges of demythologization in relation to the study of medieval Spanish history.